Combining P and Zn fertilization to enhance yield and grain quality in maize grown on Mediterranean soils - Antonio Rafael Sánchez-Rodríguez (Nature Portfolio, 2021)
Abstract The main aim of this study was to elucidate the effect of individual and joint fertilization with P and Zn on maize plants grown on typical Mediterranean soils with a limited Zn availability. For this purpose, we examined the effects of P and Zn fertilization individually and in combination on growth, yield and grain protein content in maize grown in pots filled with three different Mediterranean soils (LCV, FER and INM). Phosphorus and Zn translocation to grain was impaired, and aboveground dry matter and yield at harvest reduced by 8–85% (LCV and FER), in plants treated with Zn or P alone relative to unfertilized (control) plants. In contrast, joint fertilization with P and Zn enhanced translocation of these nutrients to grain and significantly increased aboveground dry matter (30% in LCV, 50% in FER and 250% in INM) and grain Zn availability in comparison with control plants. Also, joint application of both nutrients significantly increased grain P (LCV) and Zn (LCV and FER) use efficiency relative P and Zn, respectively, alone. Yield was increased between 31% in LCV and 121% in FER relative to control plants, albeit not significantly. Fertilization with P or Zn significantly influenced the abundance of specific proteins affecting grain quality (viz., storage, lys-rich and cell wall proteins), which were more abundant in mature grains from plants fertilized with Zn alone and, to a lesser extent, P + Zn. Sustainable strategies in agriculture should consider P–Zn interactions in maize grown on soils with a limited availability of Zn, where Zn fertilization is crucial to ensure grain quality.